Cholesteric solid spherical microparticles: chiral optomechanics and microphotonics. Issue 1 (2nd January 2016) - Hernández, R. J.; Provenzano, C.; Mazzulla, A.; Pagliusi, P.; Viola, M.; Cipparrone, G.
ABSTRACT: This article reviews the main results from the investigations performed on solid chiral microparticles based on polymerized cholesteric droplets. The procedures of particles generation, the structural characterization, optomechanics and microphotonics investigations are shown. The aim of this work is to give a picture of the innovation introduced by exploring the combination of chirality, self-organization and solid structure.